2020
DOI: 10.1002/ccd.29392
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser coronary atherectomy for uncrossable coronary lesions. A multicenter registry

Abstract: Objectives: To assess the efficacy and safety of excimer laser coronary atherectomy (ELCA), as well as, the long-term outcomes and the factors associated with ELCA failure in uncrossable lesions.Background: Uncrossable lesions constitute a challenge for percutaneous coronary intervention.Methods: This multicenter registry included 126 patients with 126 uncrossable lesions. Study endpoints were ELCA success, technical success and a composite of cardiac death, myocardial infarction (MI), and target-lesion revasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In addition, although the selection of a newer generation of DES and the optimization of postprocedural minimal lumen diameter to obtain optimal acute angiographic results could improve long-term outcomes, these approaches are required for all target lesions. Unlike other contributors, CAC could be identified and quantified before the procedure and be theoretically ‘modifiable’ for better stent deployment and expansion during the procedure with the use of more aggressive interventional approaches, such as cutting ballooning [21], rotational atherectomy [21,22], orbital atherectomy [23], excimer laser coronary atherectomy [24] and coronary intravascular lithotripsy [25]. These approaches could be planned even before conducting the invasive procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although the selection of a newer generation of DES and the optimization of postprocedural minimal lumen diameter to obtain optimal acute angiographic results could improve long-term outcomes, these approaches are required for all target lesions. Unlike other contributors, CAC could be identified and quantified before the procedure and be theoretically ‘modifiable’ for better stent deployment and expansion during the procedure with the use of more aggressive interventional approaches, such as cutting ballooning [21], rotational atherectomy [21,22], orbital atherectomy [23], excimer laser coronary atherectomy [24] and coronary intravascular lithotripsy [25]. These approaches could be planned even before conducting the invasive procedure.…”
Section: Discussionmentioning
confidence: 99%
“…RA can be very useful in this setting by debulking lesions with severe calcification to improve vascular compliance and device trafficability. A recent multicentral study suggested that excimer laser coronary atherectomy was effective in uncrossable CTO lesions (21). Although there is a lack of sufficient practice, we are optimistic about its prospects.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, ELCA is commonly used in highly complex lesions, including saphenous vein grafts, calcifications, tortuosity (moderate/severe), in-stent restenosis, and bifurcations, and carries the dual benefit of low rates of major adverse cardiovascular complications and high technical and procedural success rates[ 5 , 6 ]. We present the first case of a severe calcified ostium lesion treated with ELCA and balloon dilatation.…”
Section: Discussionmentioning
confidence: 99%